Autoimmune Encephalitis in Long-Standing Schizophrenia: A Case Report - Vaux, Amy; Robinson, Karen; Saglam, Burcu; Cheuk, Nathan; Kilpatrick, Trevor; Evans, Andrew; Monif, Mastura (Frontiers in Neurology, 2022)
Anti-NMDA Antibody (Ab) mediated encephalitis is an autoimmune disorder involving the production of antibodies against NMDA receptors (NMDAR; N-Methyl-D-aspartate receptors) in the central nervous system (CNS) that leads to neurological or psychiatric dysfunction. Initially described as a paraneoplastic syndrome in young women with teratomas, increased testing has found it to be a heterogeneous condition that affects both sexes with varying clinical manifestations, severity, and aetiology. This case report describes a 67-year-old man with a 40-year history of relapsing, severe, treatment-refractory schizoaffective disorder. Due to worsening of his condition during a prolonged inpatient admission for presumed relapse of psychosis, a revisit of the original diagnosis was considered with extensive investigations performed including an autoimmune panel. This revealed anti-NMDAR antibodies in both serum and cerebrospinal fluid (CSF) on two occasions. Following treatment with intravenous immunoglobulin (IVIg) and methylprednisolone, he demonstrated rapid symptom improvement. This is a rare case of a longstanding psychiatric presentation with a pre-existing diagnosis of schizoaffective disorder subsequently found to have anti NMDA Ab mediated encephalitis. Whether the case is one of initial NMDA encephalitis versus overlap syndrome is unknown. Most importantly this case highlights the need for vigilance and balanced consideration for treatment in cases of longstanding psychiatric presentation where the case remains treatment refractory to antipsychotics, or when atypical features including seizures, and autonomic dysfunction or focal neurology, are observed.